2019
DOI: 10.3390/cancers11070987
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization of Hepatocellular Carcinoma with Idarubicin-Loaded Tandem Drug-Eluting Embolics

Abstract: : Objective: To describe the responses, toxicities and outcomes of HCC patients treated by transarterial chemoembolization (TACE) using idarubicin-loaded TANDEM beads. Materials and Methods: Seventy-two consecutive patients (mean age: 71 years (58–84 years)) with HCC were treated by TACE using idarubicin-loaded TANDEM in a first line, over a five-year period. Most patients (89%) had liver cirrhosis classified as Child–Pugh A (90%). BCLC B classification applied in 85% of cases. Baseline tumor burden was limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…However, it remains longer than the median 6.6 months PFS reported by Guiu and colleagues with idarubicin, and longer than the 7.7-month PFS reported by Roth and colleagues when comparing idarubicin and doxorubicin [ 31 , 32 ]. TACE with idarubicin has gained a lot of interest in recent years and the results obtained in our study are among the best reported so far [ 15 , 16 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, it remains longer than the median 6.6 months PFS reported by Guiu and colleagues with idarubicin, and longer than the 7.7-month PFS reported by Roth and colleagues when comparing idarubicin and doxorubicin [ 31 , 32 ]. TACE with idarubicin has gained a lot of interest in recent years and the results obtained in our study are among the best reported so far [ 15 , 16 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 57%
“…LifePearl™ can be loaded with various anthracyclines, such as doxorubicin, epirubicin and idarubicin, for DEM-TACE in the treatment of HCC. The data on safety and efficacy of idarubicin started to emerge only in recent years [ 15 , 16 ]; epirubicin is the preferential drug in some countries, while doxorubicin remains the most used drug for HCC treatment. The main purpose of this study was to assess tolerance and toxicity (hepatobiliary and systemic), safety and tumor response after DEM-TACE with LifePearl™ microspheres loaded with anthracyclines in a real-life setting.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, British BTG plc developed and launched DC Bead, the world's first drug-eluting bead onto which doxorubicin and irinotecan can be loaded, which then quickly obtained approval from various European and American organizations for application in the treatment of primary and secondary liver cancer (15)(16)(17)(18). In the years that followed, several drug-eluting microspheres were launched successively, including HepaSphere (19), CalliSpheres (20) and TANDEM (21). Drug-eluting microspheres come in a variety of sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended maximum dose of doxorubicin and irinotecan is 50 mg/mL. Several recent randomized controlled trials and retrospective cohort studies have shown the clinical values of drug-loadable TANDEM using microspheres of different sizes with improved pharmacokinetic characteristics 29 31 . However, most studies have used microspheres of a specific diameter range or two sizes simultaneously for HCC treatment 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%